Early nasogastric tube feeding in optimising treatment for hyperemesis gravidarum: the MOTHER randomised controlled trial (Maternal and Offspring outcomes after Treatment of HyperEmesis by Refeeding). Issue 1 (December 2016) - Grooten, Iris; Mol, Ben; van der Post, Joris; Ris-Stalpers, Carrie; Kok, Marjolein; Bais, Joke; Bax, Caroline; Duvekot, Johannes; Bremer, Henk; Porath, Martina; Heidema, Wieteke; Bloemenkamp, Kitty; et al.
Abstract Background Hyperemesis gravidarum (HG), or intractable vomiting during pregnancy, is the single most frequent cause of hospital admission in early pregnancy. HG has a major impact on maternal quality of life and has repeatedly been associated with poor pregnancy outcome such as low birth weight. Currently, women with HG are admitted to hospital for intravenous fluid replacement, without receiving specific nutritional attention. Nasogastric tube feeding is sometimes used as last resort treatment. At present no randomised trials on dietary or rehydration interventions have been performed. Small observational studies indicate that enteral tube feeding may have the ability to effectively treat dehydration and malnutrition and alleviate nausea and vomiting symptoms. We aim to evaluate the effectiveness of early enteral tube feeding in addition to standard care on nausea and vomiting symptoms and pregnancy outcomes in HG patients. Methods/Design The MOTHER trial is a multicentre open label randomised controlled trial (www.studies-obsgyn.nl/mother ). Women ≥ 18 years hospitalised for HG between 5 + 0 and 19 + 6 weeks gestation are eligible for participation. After informed consent participants are randomly allocated to standard care with intravenous rehydration or early enteral tube feeding in addition to standard care. All women keep a weekly diary to record symptoms and dietary intake until 20 weeks gestation. The primary outcome will be neonatal birth weight. Secondary outcomes will be the 24-h Pregnancy Unique Quantification of Emesis and nausea score (PUQE-24), maternal weight gain, dietary intake, duration of hospital stay, number of readmissions, quality of life and side-effects. Also gestational age at birth, placental weight, umbilical cord plasma lipid concentration and neonatal morbidity will be evaluated. Analysis will be according to the intention to treat principle. Discussion With this trial we aim to clarify whether early enteral tube feeding is more effective in treating HG than intravenous rehydration alone and improves pregnancy outcome. Trial registration Trial registration number:NTR4197 . Date of registration: October 2nd 2013.